More than "Add Women and Stir" - A Conversation with Karen Klitgaard Povlsen - Kjær, Katrine Meldgaard; Leer, Jonatan (Kvinder, Køn & Forskning, 2017)
More Than ‘Add Women and Stir’ – A Conversation with Carole Counihan. Food studies and the study of food and gender have been particularly strong scholarly currents in the US. Here, anthropologist Carole Counihan was one of the first scholars to work with the food-gender intersection. Over the past four decades, she has continued to work with the area in an array of different contexts. In this interview, Counihan describes how she has worked with the gendering of food culture. Along the way, she also offers her perspectives on working in changing academic environments and shares her suggestions for future areas of research.